The book that ate my brother - Dahl, Michael; Kendall, Bradford (Mankato, MN : Capstone, 2011)
Jack writes a letter to the Librarian because he needs help, his brother has been eaten by a book.
Stone Arch Books.
4-8.
9-13.
2.8.
330
J
Keywords: Brothers -- Juvenile fiction; Books and reading -- Juvenile fiction; Horror tales; Brothers -- Fiction; Books and reading -- Fiction; Horror stories; Brothers -- Fiction; Books and reading -- Fiction; Horror fiction